Rainfall extremes modeling under shortage of data and uncertainty in the Pampean region (Argentina) - Puricelli, Marino Marcelo (Universidad de La Rioja, España, 2024)
The assessment of the surface runoff capacity of storms is essential for the design of drainage infrastructure, for the management of rainfall excesses and the control of soil erosion. The knowledge of precipitation intensity values at scales larger than the daily is a key in this process. However, the available information in the region is reduced, due to the lack of instruments and historical data. An alternative to solve this problem consists of the search of mathematical relations for the scale change from daily values, more common and available, to sub-hourly values, necessary for the estimation of runoff volumes in small basins as well as erosive power of rainfall. The first results obtained in the experimentation and search of mathematical relations for the change of temporal scale for values of intensity of precipitation, valid for a wide territory with clear climatic and ecological variability are presented in this paper. The main objective of this work was to investigate the property of scale invariance in rainfall intensity and its application to the construction of IDF curves by simple scaling. The regionalization of the values obtained in the areas of study was established as a complementary objective. The hypothesis of the scale invariance and the possibility of applying simple scaling to precipitation intensity values have been verified using both pluviographic and pluviometric data recorded over the Argentina's Pampean region in climatically and ecologically different localities. The present work provides the criteria and reference values for the construction and updating of the IDF curves in the region, where they are highly necessary, leading to advances in hydrology in areas with little or no rainfall information. The results provide new evidence on scaling relations in hydrological variables, which are useful for application in cases where reference information is scarce. This contributes to the knowledge of local precipitation characteristics and provides reference values to be used in practical applications.